Circular concrete filled steel tubes made of eco-concrete with limestone fines added as cementitious paste replacement. (December 2020) - Cai, Yancheng; Kwan, Albert K.H.; Li, Leo G.
Abstract: One effective method of reducing the cement content and carbon footprint so as to produce eco-concrete is to add limestone fines to replace an equal volume of cementitious paste. This method is herein applied to the concrete infill of concrete filled steel tubes (CFSTs). To study the properties of the eco-concrete so produced and the effects of using such eco-concrete on the axial performance of CFSTs, circular steel tubes infilled with such eco-concrete or conventional concrete had been tested under axial compression. The steel tubes were of grade S355 and had diameters ranging from 88.9 to 168.3 mm, whereas the concrete infills had water/cement ratio of 0.35–0.55, and limestone fines content by concrete volume of 8%. The results revealed that at same water/cement ratio, the eco-concrete generally had higher compressive strength and the CFSTs infilled with the eco-concrete had better axial performance. However, at same concrete strength level, the CFSTs infilled with the eco-concrete had similar axial performance. Lastly, the test results were compared with predictions by the existing design equations in various codes and it was found that the existing design equations may also be applied to CFSTs infilled with such eco-concrete.